Aspek Budaya dan Sosial dalam Komunikasi dan Profesionalisme Medis - Astrid Pratidina Susilo (Keluwih: Jurnal Sosial dan Humaniora, 2021)
Abstract— Medical communication and professionalism are central issues in clinical practice. Both are highly influenced by context such as cultural and social aspects. In medical education, a lot of studies about communication and professionalism have been conducted in Western setting and may not be fully applicable for other cultural or social context. This article aims to introduce several evidence from non-Western context in the area of medical communication and professionalism and discuss their applicability. We will use the study from Hofstede et al. about cultural domains as a theoretical basis. We will also present different studies on communication and professionalism conducted in Asia, such as from Indonesia and Japan, highlight some differences, and discuss how they may influence the medical communication and professionalism. We will provide practical examples on how to use these body of evidence in communication skills training and other area of medical education. Finally, we will discuss some ideas to strengthen future research initiatives from our context. Keyword: Asia, communication, culture, education, professionalism Abstrak— Komunikasi medis dan profesionalisme adalah masalah sentral dalam praktik klinis. Keduanya sangat dipengaruhi oleh konteks seperti aspek budaya dan sosial. Dalam pendidikan kedokteran, banyak penelitian tentang komunikasi dan profesionalisme telah dilakukan di lingkungan Barat dan mungkin tidak sepenuhnya dapat diterapkan untuk konteks budaya atau sosial lainnya. Artikel ini bertujuan untuk memperkenalkan beberapa bukti dari konteks non-Barat di bidang komunikasi medis dan profesionalisme serta membahas penerapannya. Kami akan menggunakan karya Hofstede et al tentang ranah budaya sebagai dasar teoritis. Kami juga akan menyajikan berbagai studi tentang komunikasi dan profesionalisme yang dilakukan di Asia, seperti dari Indonesia dan Jepang, menyoroti beberapa perbedaan, dan membahas bagaimana pengaruhnya atas komunikasi medis dan profesionalisme. Kami akan memberikan contoh praktis tentang bagaimana menggunakan bukti-bukti ini dalam pelatihan keterampilan komunikasi dan bidang pendidikan kedokteran lainnya. Terakhir, kami akan membahas beberapa ide untuk memperkuat inisiatif penelitian di masa depan dari konteks Indonesia. Kata kunci: Asia, komunikasi, budaya, pendidikan, profesionalisme